Weight status and its relationship with corona fear, food diversity, and physical activity in children and adolescents - Mojgan Sohoolian; Ahad Alizadeh; Mohammad Reza Shiri-Shahsava; Mohammad Amerzadeh; Alireza Razzaghi; Maryam Javadi (Wolters Kluwer Medknow Publications, 2023)
Introduction: The social restrictions implemented during the COVID-19 pandemic likely influenced children's and adolescent's lifestyles and nutrition. This study sought to assess student dietary quality and physical activity levels during the pandemic, as well as examine their association with overweight risk. Methods: Four hundred and fifty-eight students aged 7-12 years old in Karaj, Iran, completed online self-administered questionnaires assessing diet, physical activity, and coronavirus fear. Using Kant's method and the Food Frequency Questionnaire, we obtained diversity scores for five food groups. Data were analyzed using R statistical software. Statistical significance was set at P < 0.05. Results: The mean dietary diversity score (DDS) was the lowest for the meat group and highest for the fruit group. A significant inverse relationship was observed between the meat group diversity score and student weight status (P = 0.02). The interaction of coronavirus fear and weight status with the meat group DDS was also significant in multivariate adjustment modeling (P = 0.018). Among overweight students, body mass index had a meaningful negative correlation with physical activity levels (r = −0.018, P = 0.016). In addition, a significant inverse association was detected between coronavirus fear and physical activity in univariate modeling (β = −145.47, 95% confidence interval: −248.81-−42.12, P ≤ 0.006). Conclusion: A significant association between coronavirus fear and reductions in physical activity as well as weight gain was observed. The study group also did not demonstrate sufficient dietary diversity. Therefore, we recommend promoting diet variety and physical activity for students as part of health-focused school curricula.